KETERLIBATAN PEREMPUAN DALAM MUSRENBANG TINGKAT DESA KOTA BANDA ACEH - Ali, Chaidir (Al-Ijtima`i: International Journal of Government and Social Science, 2023)
The Development Planning Conference is a means for government at all levels to gather development aspirations in all areas of community life. However, unfortunately, so far Musrenbang activities at all levels still face low participation from women's groups, in fact their participation tends to be considered only symbolic. As a consequence, many planned programs are gender biased, where discussions are dominated by infrastructure and economic development plans. Based on this, the author is interested in comparing the level of women's participation in the Village Development Planning Conference (Musrenbangdes) in Gampong Beurawe and Gampong Jawa which have quite different levels of development to see the level of women's participation in Musrenbangdes in the two gampongs. Apart from that, we will see what factors influence high or low participation in the two gampongs. This research uses a comparative analysis method with a qualitative approach and data collection techniques in the form of observation, interviews and documentation obtained from the two variables studied. The results of this research show that the level of women's participation in Gampong Beurawe is better than the level of women's participation in Gampong Jawa in the Musrenbangdes in both gampongs. The factors that influence high and low levels of participation are educational, cultural and political factors.